(untitled) - Clarke, Tracylee (LosAngeles, 2016)
Environmental Conflict Management introduces students to the research and practice of environmental conflict and provides a step-by-step process for engaging stakeholders and other interested parties in the management of environmental disputes
Keywords: Quản lý môi trường,Chính sách môi trường,Environmental management,Environmental policy